Driving β2- While Suppressing α-Adrenergic Receptor Activity Suppresses Joint Pathology in Inflammatory Arthritis - Bellinger, Denise L.; Wood, Carlo; Wergedal, Jon E.; Lorton, Dianne (Frontiers in Immunology, 2021)
Objective: Hypersympathetic activity is prominent in rheumatoid arthritis, and major life stressors precede onset in ~80% of patients, supporting a link between stress and disease onset and progression. Here, we extend previous research by evaluating how selective peripherally-acting adrenergic drugs effect joint destruction and influence immune mediation of adjuvant-induced arthritis (AA). Methods: Inflammatory arthritis was induced by complete Freund’s adjuvant in male Lewis rats. These rats then received vehicle or twice daily treatment with the -adrenergic antagonist, phentolamine (500 µg/kg) and the β2-adrenergic agonist, terbutaline (1200 µg/kg, collectively named SH1293) from day (D) of disease onset (D12) through acute (D21) and severe disease (D28). Disease progression was assessed in the hindlimbs using dorsoplantar widths, X-ray analysis, micro-computed tomography, and routine histology on D14, D21, and D28 post-immunization. Results: On D21, SH1293 significantly attenuated arthritis in the hindlimbs, based on reduced lymphocytic infiltration, preservation of cartilage, and bone volume. Pannus formation and sympathetic nerve loss were not affected by SH1293. Bone area and osteoclast number revealed high- and low-treatment-responding groups. In high-responding rats, treatment with SH1293 significantly preserved bone area and decreased osteoclast number, data that correlated with drug-mediated joint preservation. SH1293 suppressed abnormal bone formation based on reduced production of osteophytes. On D28, the arthritic sparing effects of SH1293 on lymphocytic infiltration, and cartilage and bone sparing were maintained. However, sympathetic nerves were retracted from the talocrural joint. Conclusion and Significance: Our findings support a significant delay in early arthritis progression by treatment with SH1293. These findings support that targeting sympathetic nerve activity may provide a strategy to slow disease progression.